2017
DOI: 10.1111/oik.04117
|View full text |Cite
|
Sign up to set email alerts
|

Fitness in invasive social wasps: the role of variation in viral load, immune response and paternity in predicting nest size and reproductive output

Abstract: Within any one habitat, the relative fitness of organisms in a population can vary substantially. Social insects like the common wasp are among the most successful invasive animals, but show enormous variation in nest size and other fitness‐related traits. Some of this variation may be caused by pathogens such as viruses that can have serious consequences in social insects, which range from reduced productivity to colony death. Both individual immune responses and colony‐level traits such as genetic diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 71 publications
8
50
0
Order By: Relevance
“…This method of detection carries the risk of detecting false-positives. However, two lines of evidence support our finding of an active infection in wasps: (1) not all samples were positive in the strand-specific RT-PCR assay despite being positive for virus by standard PCR, indicating that the viral replication assay was able to differentiate between inactive and active virus; (2) previously published papers have demonstrated that honeybee viruses, including DWV, replicate in a variety of insects, including Vespula wasps [8,44,54]; thus, our finding of replication is not surprising.…”
Section: (C) Viral Replicationsupporting
confidence: 77%
“…This method of detection carries the risk of detecting false-positives. However, two lines of evidence support our finding of an active infection in wasps: (1) not all samples were positive in the strand-specific RT-PCR assay despite being positive for virus by standard PCR, indicating that the viral replication assay was able to differentiate between inactive and active virus; (2) previously published papers have demonstrated that honeybee viruses, including DWV, replicate in a variety of insects, including Vespula wasps [8,44,54]; thus, our finding of replication is not surprising.…”
Section: (C) Viral Replicationsupporting
confidence: 77%
“…responses among patrilines within colonies of the polyandrous V. vulgaris but they found no differences due to patriline, perhaps due to lower sample sizes than those employed here. Our results suggest that the PPH likely explains why high colony genetic diversity is associated with high reproductive success in eusocial wasps, as found by Goodisman et al (2007) and Dobelmann et al (2017). As observed in other Vespula species (Ross 1986;Goodisman et al 2007) we found that sperm mixing must have occurred in queens' spermatheca because patrilines were evenly distributed across emergence dates resulting in increased genetic diversity within colonies.…”
Section: Dobelmann Et Al (2017) Compared Natural Viral Infection Ratsupporting
confidence: 85%
“…Sex ratios in some social wasps can show considerable variation, with some colonies rearing predominantly either queens or males in their reproductive phase (Bonckaert, van Zweden, d'Ettorre, Billen, & Wenseleers ; Greene, ). Intracolony genetic diversity in Vespula wasps caused by multiple mating of the queen has been associated with variable sex ratios and queen production (Dobelmann et al, ; Goodisman et al, ; Johnson et al, ), indicating the importance of genetic diversity within a colony. However, observations for Vespula vulgaris suggest equal production of males and queens (Archer, , ), but it is not currently known whether these ratios can shift with invasion (Gloag et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wasp colonies are annual and only produce one generation of males and new queens in late summer and autumn, and thus, the number of queen cells is a direct representation of the output of daughter queens for a queen or matriline. This estimate is commonly used to describe fitness in Vespula species (Archer, 1980;Dobelmann et al, 2017;Goodisman, Kovacs, & Hoffman, 2007) The Vespula germanica mitochondrial genome (GenBank Accession no. KR703583) was used as a reference, map generated using GenomeVx (Conant & Wolfe, 2008) [Colour figure can be viewed at wileyonlinelibrary.com] rearing predominantly either queens or males in their reproductive phase (Bonckaert, van Zweden, d'Ettorre, Billen, & Wenseleers 2011;Greene, 1984).…”
Section: Colony Characteristics and Queen Cells As An Indicator Of mentioning
confidence: 99%
See 1 more Smart Citation